(untitled) (European Journal of Marketing and Economics, 2021)
The integration of Indian economy through the channels of trade and capital flow has been accelerated over the last two decades. Even during the Covid-19 pandemic, policy stimulus continued to promote export-led growth in the economy. These decadal efforts to retain the exiting market share and capturing the new market continues to face number of challenges for India. India is presently known as one of the most important players in the global economic landscape. After the US-China trade war scenes, the outbreak of Covid-19 pandemic has questioned China’s integrity across many countries of the world. When developed countries thinking over shifting their manufacturing base out of China, attracting this large chunk of capital flight has challenged Indian government. Data shows that the aggressive policy measures taken by both the central and state government to tap the crowding out of investment from China apparently succeeding. But this is a short-term picture, will it continue in the long-run? That is questionable. The ‘Make in India’ or ‘Atmanirbhar Bharat’ initiatives, export-led growth policy stimulus during pandemic, rise in exports of food products, generic medicines, newly entered FDIs and flood of FIIs in Indian economy. All these dots need to be connected at the backdrop of India’s New Foreign Trade Policy (2021-26). This research paper would like to focus on each one of the above mentioned initiatives by the Indian government and its significance to the entire trade policy as such. Paper would also like to consider the sustainability part of these initiatives.